Point of care testing: potential for tracking disease management outcomes. - Price CP (Disease Management & Health Outcomes, 2002)
Point of care testing describes testing using handheld or benchtop technology, where the result will be used in the screening for, or the diagnosis and/or the management of, disease. It is an alternative to using the services of a centralized facility such as a laboratory.The successful use of point of care testing technology demands that the quality of the result can be assured and that a clinical and/or economic benefit can be demonstrated. As with benchtop technology, handheld technologies have features to deal with all the steps in the analytical process. The quality of the result depends on the manufacturing process of the device and the competence of the operator.The potential for clinical and/or economic benefit will exist wherever the rapid provision of the result enables a decision to be made immediately and appropriate action implemented. This may include making or ruling out a diagnosis; the latter leading to an alternative diagnostic pathway or discharge of the patient. The clinical benefits, however, will also depend on the implementation of an intervention and will be measured in terms of improved morbidity and mortality. However, in both the design of outcome studies as well as the routine management of patients, surrogate markers of outcome may be used to assess the value of the test and intervention.In patients with chronic diseases a test may be used to assess the status of the patient and the effectiveness of the intervention, thus playing an important role in maintaining patient compliance. Diabetes mellitus provides an excellent exemplar of point of care testing producing both positive clinical and economic outcomes in the management of a chronic disease. The speedy availability of results has also been shown to facilitate rapid decision making in acute medical situations such as in the emergency room and operating room.As a more patient-focussed approach to healthcare is being adopted leading to the requirement for faster access to results, as well as more testing being undertaken in the home and the primary care setting, the demand for point of care testing technology is set to increase dramatically. Changes in clinical practice will need to be made to maximize the benefits of testing to the patient and healthcare provider. Furthermore, a wider perspective will have to be adopted with regard to resource allocation because point of care testing, as a testing modality, will be expensive but the wider economic benefit will be greater.